Self-assembly of Gd3+-bound keplerate polyanions into nanoparticles as a route for the synthesis of positive MRI contrast agents. Impact of the structure on the magnetic relaxivity. Issue 38 (24th September 2018) - Elistratova, Julia; Akhmadeev, Bulat; Korenev, Vladimir; Sokolov, Maxim; Nizameev, Irek; Gubaidullin, Aidar; Voloshina, Alexandra; Mustafina, Asiya
Abstract : Correlation between the structure of keplerate polyanions and the magnetic relaxivity, stability and cytotoxicity of their complexes with Gd 3+ ions. Abstract : The present work introduces Gd 3+ complexes with giant keplerate polyanions as a promising basis for MRI contrast agents. The impact of Gd 3+ binding with different building blocks of keplerates on the magnetic relaxivity of the complexes is revealed by comparative study of the keplerates [{Mo6 O21 }12 {Mo2 O4 (OAc)}30 ] 42−, [{Mo6 O21 }12 {Mo2 O4 (HPO4 )}30 ] 72−, and [{Mo6 O21 }12 {Mo2 O2 S2 (OAc)}30 ] 42− . Unprecedentedly high longitudinal and transverse relaxivity values (up to 250 and 300 mM −1 s −1 correspondingly) are achieved for the keplerates possessing edl{Mo2 O4 (OAc)} and {Mo2 O4 (HPO4 2− )} moieties under their 1 : 1 complex formation with Gd 3+ . The transformation of the external pores from Mo9 O9 to Mo9 O6 S3 in the {Mo2 O2 S2 (OAc)}-keplerate and an increase in the Gd 3+ -to-keplerate ratio are the factors that decrease the relaxivity. The rapid degradation of the free keplerates in aqueous solutions restricts the use of the Gd 3+ -bound keplerates with 1 : 1 stoichiometry as MRI contrast agents. In this work, the optimized stoichiometry of the complexes, their self-assembly into ultra-small nanoparticles and their hydrophilic coating by a triblock copolymer are highlighted as tools for increasing both the colloid and chemical stability of the keplerate complexes. Optimal keplerate compositions have been identified to achieve a compromise of low cytotoxicity and high stability; these Gd 3+ -bound keplerates exhibit longitudinal and transverse relaxivity values (95 and 114 mM −1 s −1, respectively), well within the region of interest for MRI techniques.